Reduced expression of UPF1 promotes tumor progression through stabilizing COX-2 mRNA in nasopharyngeal carcinoma - Wu, Chun; Xiao, Ruowen; Zhang, Lin; Chen, Zixuan; Zhang, Meiyin; Li, Jiaxin; Zhou, Yufeng; Wang, Shuocheng; Jiang, Chao; Wang, Huiyun; Sun, Rui; Mai, Shijuan (Frontiers in Immunology, 2025)
BackgroundUPF1 (upframeshift 1) is the core factor in the nonsense-mediated mRNA decay (NMD) pathway. UPF1 is dysregulated in multiple human malignancies and may play a role in cancer progression. However, the expression level and function of UPF1 in nasopharyngeal carcinoma (NPC) have remained undocumented until now.MethodsUPF1 expression in NPC tissues was evaluated by using qRT–PCR and immunohistochemistry assays. In vitro and in vivo experiments were performed to examine the effects of UPF1 on NPC cells. NMD targets were identified by RNA-seq and RNA stability analysis. Rescue experiments were employed to reveal the underlying molecular mechanisms that mediate the tumor suppressive role of UPF1. The effects of UPF1 knockdown NPC cells on macrophages and T cells were detected by using an indirect coculture system.ResultsUPF1 expression was significantly downregulated in NPC tissues and correlated with a poor prognosis. UPF1 overexpression inhibited NPC cell growth and metastasis both in vitro and in vivo. COX-2 and PD-L1 were identified as the key targets of UPF1-mediated NMD in NPC. Reduced expression of UPF1 activated the ERK/MAPK and JAK2/STAT3 pathways and enhanced NPC cell viability through upregulation of COX-2. Moreover, coculture with UPF1-knockdown NPC cells promoted macrophage M2 polarization and migration and suppressed CD8+ T-cell activation.ConclusionsOur findings suggest that reduced expression of UPF1 in NPC might contribute to tumor progression.